Is the Dog a Possible Reservoir for Cutaneous Leishmaniasis in Suriname? - Alida Kent; Prakash Ramkalup; Dennis Mans; Henk Schallig (Journal of Tropical Medicine)
Cutaneous leishmaniasis (CL) is an emerging disease in Suriname, with at least 200 cases per year. Little is known about the biology of CL in the country. The most important parasite species is Leishmania Viannia guyanensis, but possible vectors and reservoirs are hardly incriminated. In the present study, it was investigated whether the dog could possibly be a zoonotic reservoir for the disease in Suriname. Forty-seven dogs were examined for overt clinical signs of leishmaniasis, and blood samples were collected on filter paper for serology (direct agglutination test) and molecular biology (by polymerase chain reaction). Three dogs had clinical signs that could be compatible with canine cutaneous leishmaniosis: dermatitis (two) or nasal lesion (one). Two dogs were seropositive with DAT (titre > 1 : 1600), and three animals had a borderline titre (1 : 800). All other animals (n=42) were DAT negative. PCR analysis found Leishmania DNA equivalent to 1 parasite per mL in only one dog at a first round of analysis, but this animal was negative after retesting. The clinical, serological, and molecular data show some preliminary lines of evidence that canine leishmaniosis is present in Suriname, but further studies are needed to incriminate the reservoir, including a possible sylvatic cycle.